Atención del requerimiento de medicamentos psicotrópicos y estupefacientes solicitados por establecimientos de salud en las redes asistenciales de EsSalud La Libertad - Alfaro Mauricio, Judith Giovana (2019)
A study was carried out whose purpose was to evaluate the attention of the requirement of psychotropic and narcotic drugs requested by health establishments in the health care networks of EsSalud La Libertad, applied a descriptive research in which 36 pharmaceutical establishments participated.It was made in the specialized central warehouse of EsSalud La Libertad. The results show the lack of compliance in the attention of the requirement of psychotropic and narcotic drugs requested by health establishments in the welfare networks of EsSalud La Libertad. Therefore, it is concluded that 80.6% of the psychotropic medication requirements requested by health facilities in the health care networks of EsSalud La Libertad were not attended and 19.4% was attended. The 30% of attention to the requirement of narcotic drugs requested by health facilities in the health care networks of EsSalud La Libertad were not attended and 70% was attended